Application of tailor rolled blanks in optimum design of pure electric vehicle crashworthiness and lightweight. (April 2021) - Yu, Luxin; Gu, Xianguang; Qian, Lijun; Jiang, Ping; Wang, Wei; Yu, Ming
Abstract: At present, one of the promising solutions to the energy crisis and environmental protection is to widely use pure electric vehicles (PEV). It is noted that lack of range limits the wide use of PEV, in which lightweight can effectively improve the range of PEV. Lightweight and crashworthiness signify two main challenges facing in vehicle industry, which often conflict with each other. The tailor rolled blank (TRB) structure, as a novel configuration, has a great potential to achieve lightweight and improve the crashworthiness. In this study, a series of TRB structures are applied to the front-end components of PEV for the design optimization of vehicle crashworthiness and lightweight. A full-scale finite element (FE) model of PEV is first constructed and validated by physical test. Then the TRB FE models of vehicle front-end components are established to replace the corresponding conventional uniform thickness (UT) structures. Based on the vehicle model with TRB structures, the safety performance of vehicle in full frontal impact is analyzed by FE method. The results show that, compared with the UT design, the front-end components with TRB structures can improve the crashworthiness of vehicle to a certain extent. In order to determine the optimized geometric distribution of TRB structures, a multi-objective design optimization procedure is implemented for the vehicle crashworthiness and lightweight design with UT and TRB structures. On the basis of the Kriging (KRG) model and the multi-objective particle swarm optimization (MOPSO) algorithm, the weight of TRB structures is reduced and the energy absorption is increased relative to the UT design, which indicates the efficient improvement of the vehicle crashworthiness. Highlights: The basic principle of lightweight design of vehicle structure is described systematically. TRB technology is applied to several parts of front-end parts of pure electric vehicles. he optimization method is used to search theTRB structure thickness distribution.